Evaluation of Health-related Internet Use in Germany - Birkmann, C.; Dumitru, R. C.; Prokosch, H.-U. (Methods of Information in Medicine, 2006)
Objective: An eHealth survey was conducted in a major Bavarian region in order to evaluate health-related Internet use in Germany.Methods: A specific questionnaire was developed by the authors to collect sociodemographic data as well as data on general and health-related Internet use. This questionnaire was distributed to patients visiting medical practices in the above mentioned Bavarian region.Results: Whereas many Internet users look for health-related information and products on the Internet, more advanced web-based techniques such as chat rooms and electronic patient records are hardly used.Conclusions: Although modern information technologies have the potential to enable citizens to handle their own health-related information in a self-determined and informed manner, at present the general population in Germany is hardly taking this opportunity.
Keywords: eHealth; evaluation; Internet